Do Certain Flavonoid IMPS Have a Vital Function? - Seigler, David S.; Friesen, J. Brent; Bisson, Jonathan; Graham, James G.; Bedran-Russo, Ana; McAlpine, James B.; Pauli, Guido F. (Frontiers in Nutrition, 2021)
Flavonoids are a vast group of metabolites that are essential for vascular plants physiology and, thus, occur ubiquitously in plant-based/-derived foods. The solitary designation of thousands of known flavonoids hides the fact that their metabolomes are structurally highly diverse, consist of disparate subgroups, yet undergo a certain degree of metabolic interconversion. Unsurprisingly, flavonoids have been an important theme in nutrition research. Already in the 1930s, it was discovered that the ability of synthetic Vitamin C to treat scurvy was inferior to that of plant extracts containing Vitamin C. Subsequent experimental evidence led to the proposal of Vitamin P (permeability) as an essential phytochemical nutrient. However, attempts to isolate and characterize Vitamin P gave confusing and sometimes irreproducible results, which today can be interpreted as rooted in the unrecognized (residual) complexity of the intervention materials. Over the years, primarily flavonoids (and some coumarins) were identified as having Vitamin P-like activity. More recently, in a NAPRALERT meta analysis, essentially all of these Vitamin P candidates were identified as IMPs (Invalid/Improbable/Interfering Metabolic Panaceas). While the historic inability to define a single compound and specific mode of action led to general skepticism about the Vitamin P proposition for “bioflavonoids”, the more logical conclusion is that several abundant and metabolically labile plant constituents fill this essential role in human nutrition at the interface of vitamins, cofactors, and micronutrients. Reviewing 100+ years of the multilingual Vitamin P and C literature provides the rationales for this conclusion and new perspectives for future research.